Managing Investment Climate Reforms: Viet Nam Case Study - Mallon, Raymond (Washington, DC: World Bank, 2012)
The objective of this study is to learn about Viet Nam's experience with reforms aimed at facilitating private entry into business. The focus of the analysis is the Enterprise Law reform and related reforms to promote domestic private sector development. The study aims to understand how the reform process itself was managed, what have been the results, and what lessons have been learned.